PERTANGGUNGJAWABAN PIDANA KORPORASI DALAM ILLEGAL FISHING DI INDONESIA (STUDI KASUS PUTUSAN NOMOR 05/PEN.PID.SUS/2015/PN.AMB) - Hengki Purnata; Zulfikar Jayakusuma; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Corporate criminal liability in illegal fishingin Indonesia is contained in Article 101 of Law Number 31 of 2004 in conjunction with Law Number 45 of 2009 concerning Fisheries which states that if the criminal act is committed by a corporation, the corporation is also subject to criminal sanctions through its management. And in reality in Decision Number 05 / Pen.Pid.Sus / 2015 / PN.Amb and Decision Number 01 / Pid.Sus / Prk / 2015 / PN.Amb, corporations are not subject to criminal sanctions or alternative sanctions. So that the decision Number 05 / Pen.Pid.Sus / 2015 / PN.Amb and also in the Decision Number 01 / Pid.Sus / Prk / 2015 / PN.Amb must be scrutinized and studied to improve the decision.This type of research is structured with a normative juridical research type. The approach used in this study uses a normative approach, namely literature law research.The results of the research from the author show that the regulation regarding the criminal responsibility of illegal fishing committed by corporations must be further regulated that those who can be prosecuted for an illegal fishing act are not only those who are direct perpetrators in the field but also those who are directly behind them and in practice of responsibility Corporate crime related to illegal fishing crime should involve the corporation in the imposition of the punishment. It would be unfair to pass all the blame on the Fishing Master and his captain alone.Keywords: Accountability - Corporation - Illegal Fishing